Presentación infrecuente de miocardiopatía por estrés (tako-tsubo) - León Aliz, Ebrey; Goicolea Ruigómez, Javier; Jiménez-Blanco Bravo, Marta (CorSalud, 2016)
Presentación infrecuente de miocardiopatía por estrés (tako-tsubo)